Oil price increases and the predictability of equity premium - Wang, Yudong; Pan, Zhiyuan; Liu, Li; Wu, Chongfeng (Journal of Banking & Finance, 2019)
We show that increases in oil prices, rather than changes in oil prices, can predict stock returns. The revealed stock return predictability is both statistically and economically significant. The forecasting performance of oil price increases is not affected by changes in the choice of subsample, a considerable advantage over other popular predictors. We obtain greater forecasting gains by adding oil price increases as an additional predictor to univariate macro models. This forecasting improvement is also present when using multivariate information methods. The success of oil-macro models in forecasting stock returns is robust to a large battery of robustness tests. Oil price increases predict stock returns by affecting future industrial production and discount rates.